An Effect of Internet Penetration on Income Inequality in Southeast Asian Countries - Caria Ningsih; Yong-Jae Choi (International Telecommunications Society (ITS), 2018)
Income inequality has become one of the major economic policy issues in developed and developing countries alike. Among ASEAN countries we have witnessed rising income inequality in Indonesia, Lao, Singapore and Vietnam over the recent years while the other ASEAN countries, such as Cambodia, Malaysia, Philippines, and Thailand have shown more or less reduced income inequality. This study examines determinants of income inequality in Southeast Asian countries. Using panel regression analysis, this study focuses on the impact of technological change, globalization and tax policy on income inequality. This study shows that internet penetration as a proxy of technological change has reduced income inequality significantly, tax revenue to GDP ratio has also reduced income inequality, but the effect is not significant. Globalization measured by FDI and trade to GDP ratio has increased income inequality, although FDI impact is not significant. Other control variables, such as ratio of secondary education enrollment, real GDP per capita and depreciation of real exchange rate have significantly improved income inequality. On the other hand, real interest rate and inflation have affected income inequality insignificantly in ASEAN countries.
Keywords: 330; Income Inequality; Internet Penetration; Gini Index; ASEAN